Casca da batata inglesa (Solanum tuberosum) na proteção antioxidante da carne de frango - Souza, Marta Alessandra de Avila (2006)
The occurrence of lipid oxidation is considerade as one of the main factors that affect the quality of meat and chicken products. This process leads to sensorial changes, to lost of nutritional value, appearance of toxic compounds and the development of free radicaIs that are associated with a variety of human disordens. As an attempt of management this process, various research were developed as a purpose to isolate bioactive compounds, obtained from plant source, that had effective antioxidant activity. This approach has consumers' preference, and also could help in the prevention of diseases. This research evaluated the effect of extracts obtained from potato peel as antioxidants in chicken meat. It was developed two raw extracts (aqueous and purificated) were prepared and injected in the chicken meat, at 0,5% concentration. The samples were stored under freezing (-18°C), analyzed monthly (TBA and pH), along with samples without extract as a contraI, in the time of eight month. An analyses of pH, thiobarbituric acid rate (TBA), antioxidant activity and phenolics were conducted to determine the antioxidant action of raw extracts. The antioxidant activity was highly significant for two raw extracts, it was finded value between 84 and 94% of the inhibition, in the test of to accelerate oxidation in the fat The purificated extract showed a greater yield in the content of the phenolics. The two extracts were effective to control lipid oxidation in the chicken meat. The sensorial quality of meat was not affected by added of the purificated extract, while, the aqueous, induced a change in the fiavour, wich was not accepted by the sensory paneI.